UNUSUAL CAUSES OF SECONDARY VARICOSE VEINS - Bhatti, Ahsan Manzoor; Siddique, Khalid; Bashir, Riaz Anwar; Sajid, Muhammad Tanveer; Mustafa, QuratulAin; Hussain, Sye Mukarram; Shukr, Irfan; Ahmed, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Varicose veins are among the most common ailments of the affluent nations. Primarily it is considered to be caused by valvular dysfunctions, but it may be secondary to other pathologies. This study was conducted to evaluate the unusual secondary causes of varicose veins. Methods: This case-series was conducted at department of vascular surgery Combined Military Hospital Rawalpindi from January 2009 to January 2012 over a period of twoyears. All cases of varicose veins reporting to vascular surgical department CMH Rawalpindi were studied over a period of 02years. Detailed history and thorough physical examination was performed in all cases. Cases secondary to deep vein thrombosis (DVT) of limb up to common femoral vein (CFV) and pelvic malignancy were excluded. Duplex Ultrasonography (USG) was performed in all cases while CT angiography/Venography was conducted in those suspected of having secondary cause.Results: A total of 288 cases were found eligible and included in the study. Ten patients (3.47%) were having unusual secondary cause most common being traumatic arterio-venous fistula (AVF) (60% cases) followed by iliac vein thrombosis (20%). One patient had Klippel Trenaunay syndrome (KTS) and another suffered arterio-venous malformations (AVM). Conclusion: An unusual secondary varicose vein is important but rare clinical entity. Diagnosis is often delayed/overlooked and patients are mismanaged for extended period of time. Exact delineation of aetiology, prompt recognition and appropriate operative technique significantly alters outcome. Keywords: Secondary varicose veins, AVF, KTS, duplex ultrasound